MODIFICATION OF RESIN EDT-69N FOR THE PURPOSE OF MECHANICAL PROPERTIES OF PLASTICS - Краля, В.; Джоган, О.; Костенко, О. (Proceedings of National Aviation University (archive), 2012)
The epoxy matrix EDT-69N it is one of license matrix which applies by aviation industry in theCommonwealth of Independent States. This matrix created according to the standards NLGS-3 with a glanceto requirements of a self-damping. A self-damping achieved by a mixing of resin UP-631 in a recipe of amatrix EDT-69N. It led to a increasing of matrix cost and a decreasing of the physical-mechanical properties.According to current standards AP-25 the matrix EDT-69N does not ensure the compliances by requirementsof combustibility, fume evolution and toxicity of combustion products. That is why a pressing problem ofmodification of matrix EDT-69N appears for the purpose of increasing of the physical-mechanical andtechnologic properties in the prejudice of requirement of combustibility.